2006
DOI: 10.1002/biot.200600153
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of rpoB gene mutations in rifampicine‐resistant Mycobacterium tuberculosis isolates from tuberculosis patients in Belarus

Abstract: The aim of this study was to investigate the frequency, location and type of rpoB mutations in Mycobacterium tuberculosis isolated from patients in Belarus. Tuberculosis cases are increasing every year in Belarus. Moreover, resistance to anti-tuberculosis drugs, especially to rifampicine, has increased. In this study, 44 rifampicine-resistance M. tuberculosis clinical isolates (including multidrug-resistant isolates) were subjected to DNA sequencing analysis of the hypervariable region (hot-spot) of the rpoB g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
10
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 22 publications
1
10
1
Order By: Relevance
“…Based on the fingerprinting data, no indication of dual infection was found in these isolates. Dual or multiple mutations in the rpoB have been reported Kazakhstan [37], Turkey [39] Belarus [40] and South Korea [41] to mention a few.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the fingerprinting data, no indication of dual infection was found in these isolates. Dual or multiple mutations in the rpoB have been reported Kazakhstan [37], Turkey [39] Belarus [40] and South Korea [41] to mention a few.…”
Section: Discussionmentioning
confidence: 99%
“…The higher frequencies of mutation-bearing sites found in our data in codons 531, 526 and 523 can be partially compared with those isolates reported from other countries (6,9,13,20,24). Other authors have reported additional variations of nucleotide changes in codon 531 (in India, TCG3TGG or TTG; in Russia, TCG3TGG, CAG, or TGT; in China, TCG3TTG; in Japan, TCG3TTG; in Korea, TCG3TTG; and in Taiwan, TCG3TTG) and in codon 526 (in India, CAC3CTC, TAC, GAC, CGC, or ACC; in Russia, CAC3CTC, GAC, CAA, CAG, TGC, AAC, CGC, or CCC; in China, CAC3TAC; in Japan, CAC3TAC; in Taiwan, CAC3TAC and CGC; in Korea, CAC3TAC; and in Brazil, TCG3TTG) (6,7,13,17,20,30,31). In this study, we observed two nucleotide polymorphism changes in codon 531 among 12 isolates: 7 isolates (15.22%) changed from TCG3TTG (Ser3Leu), and 5 changed from TCG3TTC (Ser3Phe).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] Belarus is in southern endemic region of Europe with 20 to 30% multiple-drug resistant (MDR) isolates among 50.6 tuberculosis cases per 100,000 population. [6] Resistance to isoniazid is increasing in Belarus because 88% of hospitalized patients with drug resistant tuberculosis in Institute of Pulmonology and Tuberculosis (Belarus-Minsk, Magilev, Brest, Gomel, Horodna and Vitebsk] demonstrated resistance to at least isoniazid and rifampicine. [6,7] In United States, approximately 13% of isolates from new tuberculosis cases are resistant to one or more of the Þ rst-line anti tuberculosis chemotherapy and 1.6% of cases are resistant to both isoniazid and rifampicin, deÞ ned as MDR tuberculosis.…”
mentioning
confidence: 99%
“…[6] Resistance to isoniazid is increasing in Belarus because 88% of hospitalized patients with drug resistant tuberculosis in Institute of Pulmonology and Tuberculosis (Belarus-Minsk, Magilev, Brest, Gomel, Horodna and Vitebsk] demonstrated resistance to at least isoniazid and rifampicine. [6,7] In United States, approximately 13% of isolates from new tuberculosis cases are resistant to one or more of the Þ rst-line anti tuberculosis chemotherapy and 1.6% of cases are resistant to both isoniazid and rifampicin, deÞ ned as MDR tuberculosis. [3,8,9] Recent worldwide surveillance has demonstrated that drug-resistant strains are now widespread and are reaching alarmingly high levels in certain countries.…”
mentioning
confidence: 99%